Asynchronous destruction of marsh and forest in Neolithic age: An example from Luotuodun site, Lower Yangtze - Deng, Zeyu; Ma, Chunmei; Wu, Li; Tan, Yan; Wang, Kunhua; Lin, Liugen; Zhao, Dongsheng; Shui, Tao; Zhu, Cheng (Frontiers in Earth Science, 2023)
The natural marshland and forest landscapes in the Lower Yangtze have undergone a long history of human-induced destruction, however, little is known about the outset and process. Here we investigate the anthropogenic impact on the marsh and forest using cores near the Neolithic Luotuodun site based on palaeoenvironmental and palaeovegetation methods. We find that the marsh was disturbed by the Neolithic community at 7500 cal yr BP and destroyed at 6500 cal yr BP. Deforestations started at 6500 cal yr BP, and the original mixed broadleaf evergreen and deciduous forest was completely cleared at 4800 cal yr BP. Our results demonstrate that the Neolithic community in the Luotuodun site gave priority to the transformation of marsh in low-lying areas before deforestation. As most recent research focuses on pollen-based forest dynamics to study the terrestrial landscape change, the emergence and evolution of anthropogenic landscapes may be greatly underestimated.